Impact of beta-lactam allergy labels on bone marrow transplant patients - Benjamin M. Haxby; Kendall J. Tucker; Caitlin M. McCracken; YoungYoon Ham; Jon P. Furuno; Jessina C. McGregor (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract